Teacher Behaviours Explaining Turkish and Dutch Students’ Mathematic Achievements - Seher Yalcın (Institute of Advanced Engineering and Science, 2017)
The purpose of this study was to examine the differences between Turkish and Dutch students’ mathematics achievement and to examine the predictive level of teacher behaviours for student performance. The participants were 3210 students and principals from 168 schools in Turkey and 2541 students and principals from 156 schools in the Netherlands, who attended the Program for International Student Assessment in 2012. According to the results of the multilevel latent class and three-step analyses, for both countries, teacher behavior related to student orientation, teacher focus on student achievement and formative assessment predicted the mathematical achievement. It is seen that a high level of teacher behavior related to student orientation and formative assessment plays an important role in schools’ achievement at very low, low, and low-medium levels for Turkey and at medium and medium-high levels for the Netherlands. Furthermore, it was determined that the students who had low- or medium-level achievement were more affected by teacher characteristics/behaviours.